Ekologi Perkotaan: Telaah Ayat-Ayat Keindahan Alam sebagai Upaya Mewujudkan Livable City - Rahmadita, Mawar; Halimatussa'diyah, Halimatussa'diyah; Ilyas, Deddy (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study aims to explore the integration of spiritual values ​​in the Quran into modern city planning which has been dominated by a physical approach and tends to ignore the value of nature conservation, in order to create a livable city. This study uses a qualitative method based on literature review with a maudhu'i interpretation approach to analyze relevant verses of the Quran regarding natural beauty. The results of the study show that the verses of the Quran describe the beauty of nature as a reflection of the greatness of Allah SWT by emphasizing harmony and balance (mizan). Elements of natural beauty such as water, air, green open space, and sunlight have aesthetic, ecological, and spiritual values ​​that support environmental sustainability. The concept of a good land (baldatun tayyibah) is a guide for harmonious and sustainable urban planning. This study concludes that the concept of a livable city is in line with the values ​​of the Quran which emphasize balance, welfare, and sustainable environmental management, thus creating a livable and environmentally and socially friendly city.